2018
DOI: 10.1111/ner.12738
|View full text |Cite
|
Sign up to set email alerts
|

Muscle Control and Non-specific Chronic Low Back Pain

Abstract: ObjectivesChronic low back pain (CLBP) is the most prevalent of the painful musculoskeletal conditions. CLBP is a heterogeneous condition with many causes and diagnoses, but there are few established therapies with strong evidence of effectiveness (or cost effectiveness). CLBP for which it is not possible to identify any specific cause is often referred to as non‐specific chronic LBP (NSCLBP). One type of NSCLBP is continuing and recurrent primarily nociceptive CLBP due to vertebral joint overload subsequent t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
139
0
8

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(151 citation statements)
references
References 131 publications
4
139
0
8
Order By: Relevance
“…Among musculoskeletal disorders, low back pain (LBP) is one of the most common complaints of workers [1]. LBP not only is considered as the most common cause of the performance failure worldwide, but also it is estimated that it affects 90% of whole world population [2]. Abdulmujeeb (2017) who studied factors related to the backache in the health workers of a hospital in Uganda stated that 31% of personnel were out of work because of this problem [3] .The prevalence of LBP among adults is very high, and 70-80% of all adults experience LBP at least once in their lifetime [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among musculoskeletal disorders, low back pain (LBP) is one of the most common complaints of workers [1]. LBP not only is considered as the most common cause of the performance failure worldwide, but also it is estimated that it affects 90% of whole world population [2]. Abdulmujeeb (2017) who studied factors related to the backache in the health workers of a hospital in Uganda stated that 31% of personnel were out of work because of this problem [3] .The prevalence of LBP among adults is very high, and 70-80% of all adults experience LBP at least once in their lifetime [4].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have showed that backache is a common disease that results in a significant disability and absence from work worldwide, and it has been reported that it could increase the probability of LBP due to mental and physical stresses, poverty, and heavy workload. Its relationship with the absence from work is also reported [2,[5][6][7]. Basen (2017) evaluated the relationship between pain and work limitations and performance disability in a population of workers who had acute backache (241 patients).…”
Section: Introductionmentioning
confidence: 99%
“…This has the potential to change the load distribution on spinal structures, and thus contribute to the maintenance and/or perpetuation of pain 7. However, despite several investigations, the exact link between the level of muscle activity and CNSLBP remains unclear 7–10. The lumbar region is highly muscular, comprising subcutaneous contributions from the lumbar erector spinae ( iliocostalis, longissimus and spinalis ) and the superficial multifidus 11.…”
Section: Introductionmentioning
confidence: 99%
“…Previous reviews have attempted to synthesise these results to draw conclusions; however, these reviews have been focused on the investigation of activity within just one muscle, or during one task, for example, standing on unstable surfaces, or synthesising results drawn from one database 8 10 23 24. While these reviews do answer specific questions, there remains a gap in the literature to assess what the overall effect of CNSLBP is on lumbar paraspinal muscle activity.…”
Section: Introductionmentioning
confidence: 99%
“…Four systematic reviews have addressed therapeutic exercise as a prevention strategy, either as a post-treatment intervention or as a particular part of the intervention focusing on prevention of recurrence and duration of new episodes [ 95 , 103 105 ]. Positive effects have been reported for different types of exercise therapy spanning general strengthening [ 101 , 106 108 ], endurance training [ 109 ], direction-specific repeated movements and flexibility [ 99 , 100 , 110 , 111 ], yoga, Pilates [ 108 , 112 ], and motor control exercises [ 96 , 97 , 99 , 113 , 114 ] with a focus on specific muscles such as the transverse abdominal or multifidus muscles as compared with no treatment or ‘usual care’ [ 115 ]. No single form of exercise is clearly superior to any other, but exercise seems to be more effective in people with chronic and persistent back pain than in people with back pain of shorter duration [ 98 ].…”
Section: Resultsmentioning
confidence: 99%